Comparison of intraocular pressure measured by non-contact air puff versus Goldmann applanation tonometers in gas-filled vitrectomized eyes - Patikulsila D. (2014)
Objective: To compare intraocular pressure (IOP) measured by two different instruments, air puff tonometer (APT) versus Goldmann applanation tonometer (GAT), in gas-filled vitrectomized eyes. Design: Three-month, prospective, comparative trial. Participants: Thirty-eight patients (38 eyes), who underwent a pars plana vitrectomy (PPV) with gas injection, were enrolled in the study. Intervention: The IOP was measured by an APT, followed by GAT within 10 minutes by two different, masked investigators. Main outcome measures: IOPs were measured by two methods and then were compared. Results: Overall, there was a high correlation between both measurements (r = 0.908, p < 0.05). Using the paired t-test, IOPs measured by the APT (21.69 ± 9.28 mmHg) and GAT (22.84 ± 9.84) were not significantly different (p > 0.05). By a subgroup analysis of 17 eyes with IOP measured by a GAT of 21 mmHg or less, the APT readings (15.28 ± 4.81) and GAT readings (14.47 ± 3.89) were not significantly different (p > 0.05). Of 21 eyes, with IOP measured by a GAT of 22 mmHg or more, the APT readings (26.88 ± 8.81) were significantly lower than those obtained by the GAT (29.62 ± 7.69) (p < 0.05). Conclusion: In gas-filled vitrectomized eyes, IOP measurements obtained by an APT correlated well with those obtained by GAT, especially when the IOP was within normal range. However, in eyes with elevated IOP, the APT significantly underestimated the IOP measurement when compared to the gold standard, GAT.